Response of different population sizes to traps and effect of spinosad on the trap catch and progeny adult emergence in Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae). (March 2020) - Dissanayaka, D.M.S.K.; Sammani, A.M.P.; Wijayaratne, L.K.W.
Abstract: Tribolium castaneum is a major pest in stored products throughout the world. Male T. castaneum adults produce aggregation pheromone 4, 8-dimethyldecanal (4, 8 DMD) which is synthetically developed and available for monitoring T. castaneum populations but low trapping by 4, 8 DMD is reported. Effects of biorational insecticides on orienting to pheromone and progeny production is shown but such tests using spinosad has areas for further discovery. Therefore the objective of this research was to determine the effect of population size and spinosad exposure on the trap catch and progeny production in T. castaneum adults. In the first experiment, T. castaneum adults were released at different population sizes and the attraction to the pheromone traps was determined. The second experiment tested attraction of T. castaneum adults pre-exposed to spinosad to the pheromone traps. In the third experiment, progeny production of T. castaneum adults exposed to spinosad was assessed. The trapping of T. castaneum is increased at high population sizes and pre-exposure to spinosad while progeny was reduced on exposure to spinosad showing sex-based effects. This study concludes with management opportunities for different population levels of T. castaneum through effects of spinosad on pheromone perception and progeny production. Highlights: Pheromone traps for T. castaneum attract more adults at higher population sizes. T. castaneum adults exposed to spinosad moved to the pheromone traps more than unexposed beetles do. Exposure to spinosad reduces progeny production in T. castaneum adults in a sex-dependent manner.